Development of a flexible antenna-wristband for wearable wrist-worn infocommunication devices of the LTE standard - Semenov, Andriy; Semenova, Olena; Pinaiev, Bogdan; Kulias, Roman; Shpylovyi, Oleksandr (Technology audit and production reserves (Online), 2022)
The object of research is the process of radiation of electromagnetic waves from a flexible antenna-wristband. The subject of research is the wave parameters and directional properties of a flexible antenna-wristband. The existing problem is that it is necessary to ensure the electromagnetic compatibility of the radio frequency units of the wrist-worn infocommunication device. This problem is due to the fact that LTE/NB-IoT, Bluetooth/Wi-Fi, and GPS antennas must be placed inside the small-sized case of the infocommunication device. To solve this problem, let’s propose a simple and cheap version of a broadband flexible bracelet antenna for LTE networks, located outside the device case. As a basis for the development of a flexible antenna-wristband, the authors chose a patch antenna, which is the base of the theory of microstrip antennas. This is due to the fact that the theoretical material is well developed for the calculation and study of the patch antenna. Structurally, a patch antenna consists of an upper metal layer that emits electromagnetic waves, a solid dielectric base, and a lower metal layer that acts as a reflector. With the classical approach to constructing a patch antenna, the width and length of its upper layer are commensurate, and its lower metal layer has geometric dimensions much larger than the upper metal layer. In contrast to the classical design, the authors proposed a new shape of the patch antenna, in which the length of the upper layer of the radiation surface is much greater than its width (5–6 times), and the lower metal layer has dimensions slightly larger than the dimensions of the upper layer. The authors have developed a flexible antenna-wristband for the frequency range of 800–1300 MHz with a wave impedance of 50 ohms, 118.7×23 mm of the upper metal layer, and 124.7×25 mm of the lower metal layer. The length of the microstrip feed line of the antenna is 54.6 mm, its width is 2 mm, and the length of the insert is 51.6 mm. The flexible antenna-wristband is connected to the printed circuit board of the infocommunication device by soldering or using a mini-coaxial cable. The authors developed an experimental layout of a flexible antenna-wristband and studied its wave and directional properties. It has been established that in the frequency range 800–1300 MHz the voltage standing wave ratio coefficient of this antenna does not exceed 3.5. The flexible antenna-wristband has directional properties, which allows reducing the level of electromagnetic radiation in the direction of the human body. Об’єктом дослідження є процес випромінювання електромагнітних хвиль гнучкої антени-браслету. Предметом досліджень є хвильові параметри та спрямовані властивості гнучкої антени-браслету. Існуюча проблема полягає в тому, що необхідно забезпечити електромагнітну сумісність радіочастотних блоків, що носяться на руці інфокомунікаційного пристрою. Ця проблема зумовлена тим, що всередині малого за розміром корпусу інфокомунікаційного пристрою, що носиться на руці, потрібно розмістити антени LTE/NB-IoT, Bluetooth/Wi-Fi та GPS. Для вирішення цієї проблеми у роботі запропонований простий та дешевий варіант широкосмугової гнучкої антени-браслета для мереж стандарту LTE, яка розташована поза корпусом пристрою. За основу розроблення гнучкої антени-браслету автори обрали патч-антену, яка є базовою в теорії мікросмужкових антен. Це зумовлено тим, що для розрахунку та дослідження патч-антени добре розроблений теоретичний матеріал. Конструктивно патч-антена складається з верхнього металевого шару, що випромінює електромагнітні хвилі, твердої діелектричної основи та нижнього металевого шару, що виконує роль рефлектора. За класичного підходу побудови патч-антени ширина та довжина її верхнього шару є співрозмірними, а її нижній металевий шар має геометричні розміри значно більші за верхній металевий шар. На відміну від класичного дизайну автори запропонували нову форму патч-антени, у якій довжина верхнього шару поверхні випромінювання значно більша за її ширину (у 5–6 разів), а нижній металевий шар має розміри, що незначно більші за розміри верхнього шару. Автори розробили гнучку антену-браслет для діапазону частот 800–1300 МГц із хвильовим опором 50 Ом, що має розміри 118,7×23 мм верхнього металевого шару та 124,7×25 мм нижнього металевого шару. Довжина мікросмужкової лінії живлення антени 54,6 мм, її ширина 2 мм та довжина врізання 51,6 мм. Гнучка антена-браслет підключається до друкованої плати інфокомунікаційного пристрою за допомогою пайки або з використанням міні-коаксіального кабелю. Автори розробили експериментальний макет гнучкої антени-браслету і дослідили її хвильові та спрямовані властивості. Встановлено, що в діапазоні частот 800–1300 МГц коефіцієнт стоячої хвилі цієї антени не перевищує величини 3,5. Гнучка антени-браслет володіє спрямованими властивостями, що дозволяє зменшити рівень електромагнітного випромінювання у напрямку тіла людини.